1987
DOI: 10.1002/art.1780300911
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind, placebo‐controlled study of the treatment of the painful shoulder

Abstract: The effect of triamcinolone subacromial bursa injection versus naproxen therapy was compared in a randomized, double-blind , placebo-con trolled study of 100 patients who had painful shoulders. Outcome was compared using degree of active abduction, pain, limitation of function, and a clinical index that combined equally weighted measures of all of these. In a timeadjusted analysis, triamcinolone was superior to placebo in all clinical variables. Naproxen was superior to placebo in all variables except pain. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 13 publications
2
103
1
3
Order By: Relevance
“…26 The patients involved in our study had chronic symptoms. Regression to the mean is unlikely in such patients and has not been noted in other studies of similar populations 4,18,27,28 but it cannot positively be excluded. Spontaneous improvement and significant fluctuation of symptoms would also be unusual in such patients.…”
Section: Discussionmentioning
confidence: 72%
“…26 The patients involved in our study had chronic symptoms. Regression to the mean is unlikely in such patients and has not been noted in other studies of similar populations 4,18,27,28 but it cannot positively be excluded. Spontaneous improvement and significant fluctuation of symptoms would also be unusual in such patients.…”
Section: Discussionmentioning
confidence: 72%
“…Two studies used saline as a placebo [47,52] and 11 used lidocaine. Triamcinolone was used in seven trials [1,8,32,37,[44][45][46] (most commonly a single 40-mg dose; range, 10-80 mg). Methylprednisolone was used in six trials, most commonly a 40-mg dose (range, 25-80 mg) [2,4,38,47,51,52].…”
Section: Methodsmentioning
confidence: 99%
“…Nonoperative treatment options, including rest, activity modification, nonsteroidal anti-inflammatory medications, physical therapy, and subacromial corticosteroid injections, are all used in the initial management of rotator cuff abnormalities prior to early surgical intervention 3 . Studies have demonstrated clinical improvements in pain relief and range of motion when subacromial corticosteroid injections are used in the treatment of rotator cuff tendinosis [4][5][6] .…”
mentioning
confidence: 99%